KAJIAN LITERATUR TENTANG KEMAMPUAN MENYIMAK SISWA DENGAN MENGGUNAKAN METODE CERITA DI KELAS RENDAH - Renni Ramadhani Lubis (LPPM STKIP AL MAKSUM, 2022)
This study aims to describe the literature review of listening skills using the story method in low grades. This study uses qualitative research methods using a literature review approach. The research stages were carried out by collecting articles, reducing articles, displaying articles, discussing, and drawing conclusions. The sources of data obtained in this study were articles in national journals for the last 3 years, namely in 2019 to 2021. The results showed 15 articles that matched the topic of listening skills using the story method. The articles include listening skills which consist of 9 articles, storytelling methods which consist of 6 articles. The implementation is in accordance with the theories that have been used as references. The novelty of this research is that there is a link between one article and another that discusses the same topic. So it can be concluded that listening skills using the story method in low grades can increase student interest and learning outcomes in lower grades.